DYSTOCIA IN A DROMEDARY CAMEL WITH PROLAPSE OF INTESTINE THROUGH VAGINAL RUPTURE - KUMAR, SURENDRA; CHOUDHARY, A K; PUROHIT, G N; MEHTA, J S; KUMAR, PRAMOD (The Indian Journal of Animal Reproduction, 2023)
This article reports a case of dystocia in a 7 year old female camel with prolapse of intestines through thevaginal rupture for which cesarean section was performed.
Keywords: Caesareansection; Dromedary camel; Dystocia; Intestinal prolapse; Vaginal rupture